Upaya Peningkatan Kompetensi Guru Dalam Pengaplikasian Office 365 Melalui Diklat Online - Dwi Riyani Darma Setianingsih; Abdul Wachid BS. (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
The covid-19 pandemic occurred unexpectedly and had a tremendous impact on the world of education around the world. Likewise in Indonesia. Face-to-face learning is stopped so that teachers cannot do face-to-face with their students. Teachers must be able to carry out distance learning to the maximum. Various types of platforms can be applied by teachers as a method of remote learning, between google classtoom, schoology, edmodo, office 365 and others. Teachers can choose one of them according to the facilities and conditions in their respective schools. But have the teachers mastered it? The purpose of this research is to find out the improvement of teacher competence in the application of Office 365 through online training. Office 365 is very helpful for teachers in managing distance learning by utilizing office teams, conducting online assessments by utilizing quiz form and Class Note Book (CNB) features, creating presentations and writing reports by utilizing the sway feature. Online training is easy, time-saving and also cost-effective because it does not require transportation and accommodation costs. English translation. Office 365 Online Training results are max due to graduation based on attendance and task collection. Natural selection determines graduation. Who fights and works hard must pass. The results of this study showed the number of participants who graduated reached 92, 43% or 32 participants from the number of 35 participants who participated in the office 365 online training. Thus, it can be concluded that online training can improve teacher competence in applying office 365.